A antropotoponímia da cidade de São João del-Rei – Minas Gerais - Celso Reis Macedo (2021)
The present work aims to present an investigation urban toponymy, more specifically, anthropotoponyms, that is, the names of places that are motivated by the names of people, registered in the city of São João del-Rei, one of the largest cities eighteenth-century Minas Gerais. Several scientific works have been carried out in the lexical area, with emphasis on those who seek to understand and explain linguistic facts based on research in the area of Toponymy, branch of Onomastics which deals with the naming of proper place names. This one work is linked to the ATEMIG Project - Atlas Toponímico do Estado de Minas Gerais based at the Faculty of Letters - FALE / UFMG, which in one of its aspects study the names of places that cover the entire mining territory, aims to demonstrate a little of the linguistic-cultural contributions to the toponymic formation of the state of Minas Gerais. In this way, seeking to contribute to the lexical studies and the historical memory of the city in Minas Gerais, we selected 1022 street names for a linguistic study that were named after people. We adopted as theoretical-methodological assumptions, Dauzat (1939), Dick (1990), Seabra (2004), Faria (2017). We started from the present, from the current name of the street - seeking to know its history - and went to the past, observing if there was variation and change over the centuries. After analyzing the data, together with the historical investigation, we retrieved information relevant to the knowledge of these personalities whose names are eternalized on street signs, squares etc. We found that the choice of names of people to name places in São João del-Rei has been given, mainly, by the homage to personalities who hold political, economic, educational, religious and military power, and also by the choice of names of prominent social families, showing how conservative it is. After the research, we realized that the toponymic study is necessary if we want to know our past, our history and, also, project our future, after all, as Dick (1992, p. 22) states “the name of place plays the role of a true chronicle ”.